2018
DOI: 10.1159/000488757
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Astrogliosis in an Experimental Model of Fibromyalgia: Effect of Dexmedetomidine

Abstract: To our knowledge, this is the first study which investigates the induction of neuroinflammation in rats using an acidic-saline model of fibromyalgia. It is well known that the hippocampus has a fundamental role in pain perception, and astrocytes play a crucial role in pain signaling. Our aim is to evaluate the ability of dexmedetomidine to attenuate the inflammatory responses induced in astrocytes. In a group of healthy rats, induction of chronic muscle pain by intramuscular injection of 100 µL of acidic salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
1
2
0
1
Order By: Relevance
“…Results revealed that that RIM3, RIM4 and ASI models lead to transient spinal cord gliosis up to 4 weeks postinduction, whereas RIM6 pattern administration results in longer-lasting astro- and microgliosis up to 6 weeks. These results are consistent with previous results obtained in the short term in rat models 17 , 24 , 43 , but to our knowledge, this is the first study describing spinal cord gliosis up to 6 weeks in an RIM6 mouse model and up to 4 weeks in the ASI. Spinal cord gliosis is known to play a pivotal role in the pathogenesis of chronic pain, and glial activation is now recognized as a powerful mechanism underlying the pathogenesis of chronic pain 44 .…”
Section: Discussionsupporting
confidence: 93%
“…Results revealed that that RIM3, RIM4 and ASI models lead to transient spinal cord gliosis up to 4 weeks postinduction, whereas RIM6 pattern administration results in longer-lasting astro- and microgliosis up to 6 weeks. These results are consistent with previous results obtained in the short term in rat models 17 , 24 , 43 , but to our knowledge, this is the first study describing spinal cord gliosis up to 6 weeks in an RIM6 mouse model and up to 4 weeks in the ASI. Spinal cord gliosis is known to play a pivotal role in the pathogenesis of chronic pain, and glial activation is now recognized as a powerful mechanism underlying the pathogenesis of chronic pain 44 .…”
Section: Discussionsupporting
confidence: 93%
“…Certain systemic and organ-specific autoimmune diseases, rheumatic mainly, can cause neuroinflammation. Fibromyalgia [ 4 ], destructive joint diseases [ 6 ], and systemic lupus erythematosus [ 3 ] are a few examples. Neurodegeneration studies suggest that peripheral infection might be related to onset and progression of age-related neurodegeneration [ 24 ].…”
Section: Neuroinflammatory Diseasesmentioning
confidence: 99%
“…Удивительно, но лечение одной дозой α 2 -адренергического агониста дексмедетомидина (5 мкг/кг) смягчило эти изменения. Это исследование предполагает, что дексмедетомидин, возможно, непосредственно воздействует на астроциты, а также предполагается и его периферическое действие [22].…”
Section: нейропротективные свойства дексмедетомидинаunclassified